2022
DOI: 10.3390/su142114492
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heterogeneous Environmental Regulations on Carbon Emission Efficiency of the Grain Production Industry: Evidence from China’s Inter-Provincial Panel Data

Abstract: Examining the impact of heterogeneous environmental regulations on the carbon emission efficiency of the grain production industry will help to provide a theoretical basis and decision-making reference for achieving the goal of carbon peaking and sustainable agricultural development. Based on the panel data of 30 provinces in China, the DEA-SBM method was used to measure the grain production industry’s carbon emission efficiency from 2011 to 2019. Separating environmental regulations into formal environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…This phenomenon has been explained in existing articles, with Porter arguing that firm competitiveness stems from the ability to innovate and improve rather than from static efficiency and that stringent environmental regulations can increase firm competitiveness by stimulating innovation to offset the costs of compliance [24]. However, with more detailed and in-depth research on environmental regulation, many scholars have found that environmental regulation and carbon emission efficiency are not a simple linear relationship [25] if the heterogeneities of industry and environmental regulations are taken into account [26]. Some scholars believe that there is a U-shaped relationship between the intensity of environmental regulations and carbon reduction technology.…”
Section: Policy Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been explained in existing articles, with Porter arguing that firm competitiveness stems from the ability to innovate and improve rather than from static efficiency and that stringent environmental regulations can increase firm competitiveness by stimulating innovation to offset the costs of compliance [24]. However, with more detailed and in-depth research on environmental regulation, many scholars have found that environmental regulation and carbon emission efficiency are not a simple linear relationship [25] if the heterogeneities of industry and environmental regulations are taken into account [26]. Some scholars believe that there is a U-shaped relationship between the intensity of environmental regulations and carbon reduction technology.…”
Section: Policy Background and Literature Reviewmentioning
confidence: 99%
“…Under strong environmental regulations, enterprises have already raised their carbon emission efficiency to a high level, and the RCS will not improve the carbon emission efficiency by a large margin. Carbon emission efficiency is strongly related to the intensity of environmental regulation already in place [26], and either too high or too low a regulatory intensity can affect the policy effectiveness of RCS.…”
Section: Environmental Regulation Intensitymentioning
confidence: 99%
“…The regional economy determines the scale of regional logistics demand, while logistics supports the development of the regional economy, promoting the flow of goods, capital, and technology. This paper selects three indicators to reflect the regional economic foundation: provincial GDP, total retail sales of consumer goods, and total import and export value [24,31].…”
Section: Plos Onementioning
confidence: 99%
“…Sun Ting analyzed the development level of regional logistics in Guangxi by constructing a first-level index system from four aspects: economic foundation, logistics infrastructure construction, regional logistics demand capacity, logistics information and talent competitiveness [23]. Hang Jiang used entropy weight TOPSIS method and FSQCA method to evaluate low-carbon logistics by using panel data of 30 provinces in China from 2008 to 2021 [24]. Zhang Guangsheng selected 10 indicators from three levels: logistics demand capacity, logistics facilities and economic capacity, and logistics development potential to build a comprehensive evaluation system for regional logistics capacity [25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sangliang et al [29] and Chaoxia et al [30] have separately observed that environmental regulation promotes CO 2 emissions efficiency in urban and manufacturing industries. Within the realm of the grain production industry, Bin et al [31] reveal the relationship between formal environmental regulations and CO 2 emissions efficiency, forming a "U" curve. Furthermore, a U-shaped correlation between marine environmental regulations and carbon efficiency has been uncovered by Qiang et al [32].…”
Section: Introductionmentioning
confidence: 99%